Interactional Strategies and Anaphoric Repairs of BS Information and Communications (BSIT) Technology Students - Kevin Lacia; Julea Nathalie Ginco; Rowanne Marie Ramos Maxilom (Pusat Pelatihan, Riset, dan Pembelajaran Bahasa, 2019)
This study aimed to analyze the interactional strategies and anaphoric repairs used in the recorded pair conversations of the Bachelor of Science in Information and Communication Technology (ICT) students who were taking the course ICT 135 (Interactive English). The present research analyzed the ten recorded pair conversations. The results revealed the questions, minimal responses, and making statements predominated among the interactional strategies while the anaphoric repairs included other-initiated self-repair and self-initiated other-repair. This study provides implications to classroom interaction and use of language in interacting with other students. Future researchers can let their participants use their Mother Tongue or the Cebuano language as the language to be used in their research, regardless of the subject taken up by the participants. In using the Mother Tongue, the participants would be more comfortable in speaking providing a more natural and unrestricted flow of conversation.